Predicting habitat suitability for an endangered medicinal plant, Saussurea medusa: insights from ensemble species distribution models - Guo, Xiang; Bai, Wei; Wang, Yihua; Hao, Senliang; Zhao, Liping; Li, Xin; Guo, Zongliang; Li, Xiaoyan (Frontiers in Plant Science, 2025)
IntroductionGlobal climate change has profound impacts on alpine ecosystems, and with climate warming, alpine plants often face a substantial risk of habitat loss. Saussurea medusa Maxim., known for its significant medicinal value, is a typical alpine plant predominantly found in the high-altitude regions of Southwest China. However, the impacts of climate change on the habitat suitability of S. medusa have not been fully understood.MethodsWe simulated ensemble species distribution models to assess the spatiotemporal habitat distribution pattern of S. medusa under different climate scenarios (ssp126 and ssp585) for the periods 2040s, 2060s, and 2070s.Results and DiscussionThe results show that the suitable habitats, under near current condition, are mainly distributed in the Qinghai-Xizang Plateau of China, covering the border regions of four provinces: Xizang, Qinghai, Sichuan, and Yunnan, with a total area of 14.06×104 km2. Under future climate change scenarios, the area of suitable habitats, particularly the highly suitable habitats, is projected to contract significantly by 80.65%, accompanied by shifts in distribution centroids towards the southwest and higher altitudes in Xizang. These results indicate that the risk of S. medusa survival due to the loss of suitable habitats would persist in the future. Among the environmental factors analyzed, elevation and three bioclimatic predictors, BIO18 (precipitation of the warmest quarter), BIO12 (annual precipitation) and BIO4 (temperature seasonality), exhibit significant impacts on the potential distribution of suitable habitats for S. medusa. Our study provides an improved understanding of the potential habitat distribution dynamics of the endangered S. medusa, thereby offering a crucial reference for its conservation and sustainable management.